A REVIEW OF THE TREE PLANTING COMPONENT OF THE IMO STATE CLEAN AND GREEN PROGRAMME IN OWERRI, NIGERIA - Dominic Azuwike, Okechi; U. Ohazurike, Eudora (African Journal of Social and Behavioural Sciences, 2024)
This paper reviews the tree planting component of the Imo State Clean and Green Programme implemented 16 years ago. This is done in the context of public participation and inter-regime sustainability. Using the case of Okigwe Road Owerri, the paper aims at establishing how much observed outcome conforms to the expectation of interspaced trees lining roadways after 16 years of programme implementation. The role of participatory appraisal, appropriateness of programme design elements, aesthetics in public consciousness and tree damage and destruction were investigated and the study was guided by Ajzen’s theory of planned behaviour, Shwartz norm activation theory and Environmentally Responsible Behaviour theory of Hines and others. A survey of 133 randomly selected stakeholder including business owners, roadside artisans along the planted roadway and the general public was carried out using a structured questionnaire. Spearman’s rank correlation (P) coefficient showed among others that acceptance of the type of trees used in the programme is positively related to a strong opinion to replace disfigured and cut trees. Pearson’s chi-square showed only 18.6 percent chance of obtaining the collected data if the null hypothesis were true. The null hypothesis that there is no significant association between reasons the trees are disfigured and considerations made to allow the trees’ survival was therefore affirmed. The results reflect indifference to tree planting outcomes in the public owing largely to public non-participation and non-involvement from project design to implementation. The need for public participation in design and execution of government environmental projects is highlighted by the paper.